Understanding the History of Globally Applying Omnibus Law and Its Relevance to the Context of Indonesian Socio-Cultural Law - Irma Rachmawati Maruf; Sardjana Orba Manullang; Wiwi Yuhaeni; Kiki Amaliah; Karman Karman (Borobudur Law Review, 2023)
It is important to understand the history of laws in a country to increase awareness and legal compliance. Likewise, in the context of Indonesia, many people still do not understand the history of the omnibus law. This research aim is to study the substance of the omnibus in the context of the Indonesian law and the socio-cultural background, this importance because the Omnibus law was a relatively new phenomena and received many criticsm from Indonesian Public. This is a Juridical normative research with the library and statutory research. This study relies on scientific evidence that has been published in many literary sources such as books, academy conferences, published journal papers and other sources that discuss omnibus law and its application in Indonesia. The Job Creation Law has been endorsed and has conveyed changes to the Indonesian people's presence, considering that an excellent authentic text should have social and severe principles that apply in Indonesia without putting the presence of local social classes aside. After analytical efforts and in-depth discussions, the research concludes that all citizens must understand the history of the omnibus law in context and its relevance to the socio-cultural context of Indonesia. Thus, citizens will obtain a clear understanding and comply with the omnibus law.